COUNSELING WITH VIDEO IMPROVED TUBERCULOSIS PREVENTION KNOWLEDGE AT BERTINGKAT PERUMNAS 1 WAENA ELEMENTARY SCHOOL - Ellen Rosawita Veronica purba; Sethiana Dewi Ruben; Elisabeth Mebri (POLTEKKES KEMENKES JAYAPURA, 2022)
Tuberculosis is a global issue due to its high mortality rate, especially in developing countries. In 2020, the prevalence of positive Mycobacterium tuberculosis in Papua Province was 540 cases, and 14 were children aged 0-14 years. Tuberculosis prevention can be achieved by providing health education to increase knowledge and develop a good preventive attitude and behaviour. The study aimed to increase knowledge about tuberculosis prevention using video at Bertingkat Perumnas 1 Waena Elementary School. The study is a pre-experimental study with one group pre-post test design. Thirty samples that met the inclusion and exclusion criteria were selected by simple random sampling from a total population of 62 students in grades 4 and 5. The data were analyzed using the Wilcoxon test. The results showed a significant difference between knowledge about tuberculosis prevention before and after intervention (p=0.002). Respondents with good knowledge before the intervention were eight respondents (26.7%) increased to 17 respondents (56.7%) after the intervention, while respondents who had sufficient knowledge before the intervention amounted to 21 respondents (70%), decreased to 13 respondents (43.3%) after the intervention. After the intervention, no respondents were included in the low knowledge category. These concluded that health education using video affects the knowledge about tuberculosis prevention at SD Inpress Bertingkat Perumnas 1 Waena. Keywords: Health education, Prevention efforts, Tuberculosis, Video media